Literatura de la levedad. La prosa inicial de Felisberto Hernández - Rubio Rubio, Cecilia Verónica (2021)
In this article, whose object of study is the initial prose of the Uruguayan writer Felisberto Hernández,which goes from 1925 to 1931, and its connection with the concept of lightness proposed by Ítalo Calvino in his Six Proposals for the Next Millennium, I will begin by reviewing the state of the question, beginning with the admiring comments that Calvino himself lavished on the work of Felisberto Hernández, to later comment on the Felisbertian criticism. In a second and third moments, I will focus on lightness as literary value and on the analysis of its presence in the work of Felisberto. I risk here a definition and a characterization of the value of lightness, which Calvin presented in a fluid way. By articulating and systematizing the occurrence oflightness in this early work, my objective is to show that she makes lightness one of its characteristic features, with which - without ceasing to be singular - it can be inserted into a literary tradition that is formed both by narrators and works associated with the Latin American avant-garde, as well as by writers of the European tradition of past centuries. With this I intend to contribute to pointing out a series, a trajectory and,  ltimately, a common literary tradition that occupies a theoretical space that is still little studied and in which a work such as that of Felisberto Hernández finds a place to be united.